2018
DOI: 10.1002/mgg3.482
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of PRKN structural variations identified through whole‐genome sequencing

Abstract: BackgroundEarly‐onset Parkinson's disease (PD) is the most common inherited form of parkinsonism, with the PRKN gene being the most frequently identified mutated. Exon rearrangements, identified in about 43.2% of the reported PD patients and with higher frequency in specific ethnicities, are the most prevalent PRKN mutations reported to date in PD patients.MethodsIn this study, three consanguineous families with early‐onset PD were subjected to whole‐genome sequencing (WGS) analyses that were followed by Sange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, examples of specific mechanisms directly linking TEs with detrimental processes in neurons are also known [ 470 , 471 ]. There are also case reports about very specific TE insertions affecting certain genes relevant for neuropathology [ 363 , 472 , 473 , 474 ].…”
Section: The Role Of Neuronal Tes In Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, examples of specific mechanisms directly linking TEs with detrimental processes in neurons are also known [ 470 , 471 ]. There are also case reports about very specific TE insertions affecting certain genes relevant for neuropathology [ 363 , 472 , 473 , 474 ].…”
Section: The Role Of Neuronal Tes In Pathologymentioning
confidence: 99%
“…Whole-genome sequencing of three families with early onset PD revealed five structural variations in the PRKN gene; retrotransposon sequences were identified within 1–2 Kb of the deletions’ break points, suggesting that all identified variations might originate through retrotransposition events [ 472 ].…”
Section: The Role Of Neuronal Tes In Pathologymentioning
confidence: 99%
“…Structural variation formation is proposed to occur with non-allelic homologous recombination. LTR and non-LTR retrotransposon sequences were identified within two kilobases of the deletion break point, suggesting that the deletions may have originated due to retrotransposition events (124). The link between retroelement activation in neurodegenerative disorders is present but not fully established.…”
Section: Mobile Elements and Neurodegenerative Disordersmentioning
confidence: 99%
“…By using use whole genome sequencing, we found that the analyzed patient carries a large deletion encompassing exon 5 and two deep intronic variants, which leads to PARKIN loss. While other exon 5 deletions were previously described in PD patients 67,68 , to our knowledge the pathogenicity of deep intronic variants in the PRKN gene was never demonstrated before. The only described splicing variants (see HGMD® Professional 2023.2) are either located at the canonical splice site or within 20 nucleotides from the intron/exon junction.…”
Section: Discussionmentioning
confidence: 65%